Energy-Efficient SMPS-Based Pulse Generator for Neurostimulators - Sinduja Seshadri; Jonathan Scott (My University, 2019)
There is a need in the neuromodulation industry for a very energy-efficient pulse generator. Little data is observed in literature to develop a power efficient pulse generator that can deliver the required stimulus. A typical stimulator has a boost stage, a low-dropout (LDO) stage and an analog circuit that delivers the stimulus in the form of a pulse to the patient. Such a system is found to be ~ 40% efficient. There are two new methods that can improve this efficiency rating significantly. (1) A modification to existing pulse generator by adding microprocessors to control the output voltages of boost and LDO in the circuit, as proposed by the manufacturer; (2) a Single-Ended Primary Inductance Converter (SEPIC) based design proposed by the authors, with the input connected to a battery and the output to electrodes. Comparing with existing design, the modification offered a consistent 75% efficiency for output voltages from 3.9V to 6.6V. SEPIC had an efficiency rating of 80% to 86% across the same voltage range.
Keywords: Neuroscience and Neural Engineering